Napoleoni 1812. aasta sõjakäigu logistilised aspektid Baltimaade perspektiivis [The Logistical Aspects of Napoleon’s 1812 Russian Campaign with a Focus on the Baltic Region] - Sibul, Eric Allan (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2013)
This article explores the logistical aspects of the Grande Armée’s campaign into Russia in 1812. The questions discussed include how logistics affected the planning and execution of the campaign. Logistic considerations might well explain why French forces went eastward through Lithuania to Moscow towards the centre of the Russian Empire rather than northward (through Latvia, Estonia and Ingermanland) to capture the capital Saint Petersburg. Difficulties faced by the French included physical challenges that had an impact on logistics, such as climate, the vast distances involved and the lack of adequate roads in the Russian Empire.(Longer version of the current abstract is included in the article, starting from p 106.)